SÍNTESE E CARACTERIZAÇÃO DE ÉTERES DE GLICERINA COMO ADITIVOS OXIGENADOS PARA O DIESEL - Mendonça, Sergiane de Jesus Rocha (2010)
Currently, the growth of world production of biodiesel is generating a large surplus of glycerin, devaluing it in the market, being necessary to transform it into products of higher added value. One way of valuing the glycerin is its etherification to be used as oxygenate additives in diesel. In this work we studied the production of glycerin ethers using alcohols cyclohexanol, isoamyl, benzyl, tert-butyl, methyl and isopropyl alcohol as eterificantes in the presence of acid catalysts, acid p-toluene sulfonic acid, the ion exchange resin Amberlyst 15 and niobia and alumina catalysts modified. The reactions were performed in high-pressure reactor and flask with a reflux system. The qualitative and quantitative analysis of the obtained products were performed using the technique of Thin Layer Chromatography, Gas Chromatography with Mass Spectrometry and Infrared Spectroscopy. The reactions which have the highest incomes were those processed in the presence of Amberlyst 15 with benzyl alcohols and tert-butyl-ether yielding 60.46% and 65.68% of mono-etherified glycerin, respectively, and with the tertiary butyl alcohol butyl alcohol in the presence of alumina catalyst modified with cerium obtaining 59.45% of glycerin ethers. Samples of pure diesel were doped with the reaction products of benzyl alcohol and tert-butyl ether at a ratio of 0.5 and 5.0%, v / v, which do not significantly influence the properties of diesel.